Kadar Autoantibodi dan Manifestasi Klinis pada Pasien Nefritis Lupus Silent dan Nefritis Lupus Overt - Kusworini Handono; Atma Gunawan; Rulli Rosandi (MEDIA MEDIKA INDONESIANA, 2012)
Autoantibodies level and clinical manifestation differences between patients with silent nephritis lupus and overt nephritis lupusBackground: One of the serious clinical manifestations of SLE is the occurrence of lupus nephritis (LN). The pathogenesis of LN is still unclear. Glomerular inflammation has been associated with high levels of autoantibodies. The purpose of this study was to assess the difference of ANA, anti ds-DNA, anti-Sm antibodies and the clinical manifestations between silent lupus nephritis (SLN) and overt lupus nephritis (OLN).Subject and Methods: Subjects were forty SLE patients (diagnosed according to ARA criteria of 1997). Autoantibodies ANA was assayed with IFA, anti-dsDNA and anti-Sm levels were assayed with ELISA. The diagnosis of LN was established using clinical signs, urinary sediments pattern and kidney biopsy, and then patients classified as a silent lupus nephritis (SLN) or overt lupus nephritis (ONL). Classification of NL histopathologic pattern was established according to WHO criteria. Differences in clinical manifestations, presence of ANA, anti-dsDNA and anti-Sm levels in the SLN and OLN and NL classes were analyzed by Chi squaretest and T test. Statistical significance determined when p<0.05.Results: OLN patients showed a edema, hypertension, anemia and autoantibodies more higher than in SLN patients. The mean level of anti-dsDNA was significantly higher in patients with OLN than in SLN (285.75±41.85 vs 179.01±61.81, p<0.000). Renal biopsy on 20 OLN patients showed: 6 patients with NL grade I/II, 9 patients with NL class III/IV and 5 patients with NL class V. Moreover on 11 SLN patients there were 7 patients with NL class I/II, 3 patients with NL class III/IV and 1 patient with NL class V. The NL classIII/IV NL patients showed anti-dsDNA level higher than the class V NL (p<0.05).Conclusion: OLN patients had clinical manifestations more severe than SLN patients. NL patients with class III/IV showed the presence of anti-dsDNA more frequently and with higher levels than the class V NL. Diagnosing NL based solely on clinical signs and laboratory often is inappropriate.Keywords: SLN, OLN, NL class, autoantibodies ABSTRAKLatar belakang: Salah satu manifestasi serius LES adalah terjadinya nefritis lupus (NL). Patogenesis NL hingga saat ini masih belum jelas. Terjadinya inflamasi di glumerulus telah dikaitkan dengan tingginya kadar autoantibodi. Tujuan penelitian ini mengetahui perbedaan ANA, anti ds-DNA dan anti-Sm pada pasien dengan NL tenang (silent lupus nephritis/SLN) dan NL manifes (overt lupus nephritis/OLN).Metode: Sampel penelitian adalah empat puluh penderita LES (didiagnosis berdasarkan kriteria ARA 1997). ANA diperiksa dengan metoda IFA, anti-dsDNA dan anti-Sm menggunakan metoda ELISA. Diagnosis NL didasarkan adanya tanda klinis, sedimen urin dan biopsi ginjal dan dikelompokkan sebagai silent lupus nephritis (SLN) dan overt lupus nephritis (ONL). Klasifikasi histopatologi NL ditegakkan berdasarkan kriteria WHO. Perbedaan manifestasi klinis, adanya ANA, kadar anti-dsDNA dan anti-Sm pada SLN dan OLN serta kelas NL dianalisis dengan uji Chi square dan T tes. Signifikansi statistik ditentukan bila p<0,05.Hasil: Penderita OLN menunjukkan adanya edema, hipertensi, anemia dan autoantibodi yang lebih tinggi daripada penderita SLN. Rerata kadar anti-dsDNA nyata lebih tinggi pada penderita OLN daripada SLN (285.75±179.01 vs 41,85±61,81; p<0,000). Biopsi ginjal 20 penderita OLN menunjukkan 6 penderita dengan NL kelas I/II, 9 penderita dengan NL kelas III/IV dan 5 penderita dengan NL kelas V. Pada 11 penderita SLN terdapat 7 penderita NL kelas I/II, 3 penderita dengan NL kelas III/IV dan 1 penderita NL kelas V. Penderita dengan NL kelas III/IV menunjukkan kadar anti-dsDNA yang lebih tinggi daripada NL kelas V (p<0,05).Simpulan: Penderita OLN mempunyai manifestasi klinis yang lebih berat daripada penderita SLN. Penderita NL kelas III/IV menunjukkan adanya anti-dsDNA yang lebih sering dan dengan kadar yang lebih tinggi daripada NL kelas V. Diagnosis NL hanya berdasarkan tanda klinis dan laboratoris seringkali menimbulkan kesalahan.